Huldrych Zwingli’s Reformation Theology: Church-State Relations and Sacramental Pedagogy as a Response to The Crisis of Modern Faith Education - Nella Mariana Panjaitan (Indonesian Journal of Christian Education and Theology, 2026)
The crisis of modern faith education is characterized by religious learning that tends to be cognitive, individualistic, and insufficiently transformative, causing faith education to lose its dimensions of spiritual formation and social responsibility. In this context, the Reformation thought of Huldrych Zwingli offers an important contribution to the reconstruction of the paradigm of Christian Religious Education (CRE). This article aims to analyze Zwingli’s Reformation theology, particularly regarding church–state relations and sacramental pedagogy, as well as its relevance to the renewal of contemporary faith education. This study employs a literature review method using a historical-theological literature review approach through an examination of Zwingli’s primary works and relevant secondary sources in the fields of Reformation theology and Christian education.